Reference gene analysis and its use for kinase expression profiling in Fasciola hepatica - Houhou, Hicham (Sci Rep, 2019)
The liver fluke Fasciola hepatica causes fasciolosis, a foodborne zoonosis affecting humans and livestock worldwide. A reliable quantification of gene expression in all parasite life stages relevant for targeting by anthelmintics in the mammalian host is fundamental. The aim of this study was to define a set of stably expressed reference genes for qRT-PCR in Fasciola studies. We determined the expression stabilities of eight candidate reference genes by the algorithms NormFinder, geNorm, BestKeeper, and comparative ΔCT method. The most stably expressed reference genes for the comparison of intra-mammalian life stages were glutamyl-prolyl-tRNA synthetase (Fheprs) and tubulin-specific chaperone D (Fhtbcd). The two best reference genes for analysis of in vitro-cultured juveniles were Fhtbcd and proteasome subunit beta type-7 (Fhpsmb7). These genes should replace the housekeeping gene gapdh which is used in most Fasciola studies to date, but in fact was differentially expressed in our analysis. Based on the new reference genes, we quantified expression of five kinases (Abl1, Abl2, PKC, Akt1, Plk1) discussed as targets in other parasitic flatworms. Distinct expression patterns throughout development were revealed and point to interesting biological functions. We like to motivate using this set of validated reference genes for future F. hepatica research, such as studies on drug targets or parasite development.